Diaphragmatic Breathing Exercise dengan Menggunakan Teknik Ballon Blowing Terhadap Frekuensi Napas pada Pasien TB Paru - Rahmat Hidayat Djalil; Zainar Kasim; Chairini Chairini (Jurnal Kesehatan Amanah, 2024)
Tuberculosis is a chronic infectious disease caused by mycobacterium tuberculosis, generally patients with pulmonary TB will experience an increase in breathing frequency, this is due to fibrosis in the lung parenchyma. Airway narrowing can be fatal if it leads to impaired ventilation and oxygenation of the body. The purpose of this study was to determine the effect of diaphragmatic breathing exercise using balloon blowing technique on breathing frequency in Pulmonary TB patient at UPTD Manembo-nembo Hospital Type C Bitung. This research design uses the Pre-Experimental Design method with a one group pre-test post-test design approach. The sample was taken based on the number of respondents as many as 11 people using Purposive Sampling. Data collection is carried out by observation. After tabulating, the data was analyzed with the Wilcoxon sign rank test with a meaning level (α) of 0.05. The results showed that the most sex obtained in this study was 9 male respondents (81.8%). The conclusion in this study is the effect of diaphragmatic breathing exercise using the balloon blowing technique on breathing frequency in pulmonary tuberculosis patients (p=0.002) <α = 0.05. The results of this study are expected to be a reference for health and educational institutions in an effort to provide diaphragmatic breathing exercise using the balloon blowing technique to pulmonary tuberculosis patients.